1994
DOI: 10.1002/1097-0142(19940215)73:4<1177::aid-cncr2820730409>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Blood vessel invasion and expression of sialyl lewisx and proliferating cell nuclear antigen in stage I non-small cell lung cancer. Relation to postoperative recurrence

Abstract: Background. Recurrence in Stage I non‐small cell lung cancer was examined with respect to vascular invasion and the immunohistochemical expression of sialyldimeric Lewisx (SLX) and proliferating cell nuclear antigen (PCNA). Methods. One hundred twenty‐eight patients with Stage I non‐small cell lung cancer who had a curative resection were the subjects of this study. Using tumor tissues fixed in formaldehyde solution, blood vessel invasion (BVI) and lymphatic invasion stained with Victoria blue‐hematoxylin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 19 publications
3
46
0
Order By: Relevance
“…In contrast to ploidy, SPF was not associated with prognosis in this study. This is in agreement with the observations of some investigators, but conflicts with the results of others who have shown a correlation between survival and SPF in lung cancer [6,13,24,41].…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to ploidy, SPF was not associated with prognosis in this study. This is in agreement with the observations of some investigators, but conflicts with the results of others who have shown a correlation between survival and SPF in lung cancer [6,13,24,41].…”
Section: Discussionsupporting
confidence: 89%
“…The presence of carbohydrate receptor sLe X in tumors or serum has been associated well with poor prognosis of various cancers [12,14,16,17] and suggested no other carbohydrate epitope examined to date has equal prognostic value. sLe X expressions in colorectal and non-small cell lung cancer has been correlated with advanced disease, increased distant metastasis and decreased survival [41]. An in vitro study identified molecules capable of interfering metastatic process by inhibiting sLe X -mediated adhesion between tumor cells and activated endothelial cells [42].…”
Section: Discussionmentioning
confidence: 99%
“…It was well-documented that Lewis antigens, mainly located on the outer chains of the glycans of cell surface glycolipids or the O-linked glycans of glycoproteins, were closely related to the metastatic potential and overall prognosis of many human cancers, such as colorectal, prostate and lung cancer (Nakamori et al, 1993;Ogawa et al, 1994;Jorgensen et al, 1995). Lewis antigens are a series of fucosylated Galβ1,3/1,4GlcNAc containing oligosaccharides (sialylated or not sialylated, β1,3 linkage in type 1 chain and β1,4 linkage in type II chain), and are known to participate in the process of leukocyte infiltration during inflammation and cell adhesion during malignant cell metastasis.…”
mentioning
confidence: 99%